2011
DOI: 10.1016/j.jtcvs.2010.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of complete atrioventricular septal defect: Associations with surgical technique, age, and trisomy 21

Abstract: Objectives We sought to evaluate contemporary results after repair of a complete atrioventricular septal defect (AVSD) and to determine factors associated with suboptimal outcomes. Methods Demographic, procedural, and outcome data were obtained within 1 and 6 months after repair of complete AVSD in 120 children in a multicenter observational study from 6/04-2/06. Results Median age at surgery was 3.7 months (range, 9 days-1.1 years). Type of surgical repair was single patch (18%), double patch (72%), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
92
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 20 publications
(22 reference statements)
4
92
2
5
Order By: Relevance
“…18,19 However, a more recent multicenter cohort of patients with CAVSD did not demonstrate a higher risk for residual ventricular septal defect in patients repaired with the classic 1-patch versus the 2-patch technique. 20 In addition, the classic 1-patch technique involves dividing the common valve leaflets and suspending them from a single patch; it may result in more distortion of the valve tissue, with a higher risk for reoperation for left AV valve regurgitation. 4 However, patch technique was not found to be a significant risk factor for this complication in our series.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, a more recent multicenter cohort of patients with CAVSD did not demonstrate a higher risk for residual ventricular septal defect in patients repaired with the classic 1-patch versus the 2-patch technique. 20 In addition, the classic 1-patch technique involves dividing the common valve leaflets and suspending them from a single patch; it may result in more distortion of the valve tissue, with a higher risk for reoperation for left AV valve regurgitation. 4 However, patch technique was not found to be a significant risk factor for this complication in our series.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[11][12][13]19,22,23,30 In a study using the 2000 version of the KID to examine the role of sex as a risk factor for in-hospital mortality after pediatric cardiac surgery, DS was 1 of 4 comorbidities used as at CONS CALIFORNIA DIG LIB on January 21, 2016 http://circoutcomes.ahajournals.org/ Downloaded from independent, nonprocedural variables. The findings of this study are consistent with our findings and demonstrate lower odds of in-hospital mortality for patients with DS.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The vast majority of infants born with an AVSD also have DS [11][12][13][17][18][19][20][21] ; however, DS is not a known risk factor for morbidity and mortality after biventricular AVSD repair. 12,22 In fact, infants with DS tend to have better outcomes after surgical repair of an AVSD compared with infants without DS. [11][12][13]23 Surprisingly, little is known about the outcomes of children with DS after surgical correction of congenital cardiac defects other than an AVSD.…”
mentioning
confidence: 99%
“…A recent study by Atz and the Pediatric Heart Network (PHN) Investigators 9 reported outcomes of 120 patients who underwent repair of CAVSD at 7 centers. Adverse outcomes were negatively correlated with age at repair from birth to age 2.5 months, but did not vary by age beyond 2.5 months.…”
mentioning
confidence: 99%
“…Apart from the PHN study, 9 there are no recent large multicenter studies pertaining to surgical outcomes among infants with CAVSD. The aim of our study is to provide a descriptive analysis of contemporary multicenter experience with repair of CAVSD using data from the STS-CHSD.…”
mentioning
confidence: 99%